The Use of Flipchart Learning Media in Improving the Ability to Recognize the Letters of Hijaiyah to Children Aged 4-5 Years at Kindergarten: Penggunaan Media Pembelajaran Flipchart dalam Meningkatkan Kemampuan Mengenal Huruf Hijaiyah Terhadap Anak Usia 4-5 Tahun di TK - Achmad Kurniawan Subarkah; Dzulfikar Akbar Romadlon (Academia Open, 2022)
This article aims to describe the results of research from the use of flipchart learning media in improving the ability to recognize hijaiyah letters for children aged 4-5 years at Primagama Creative Kindergarten Sidoarjo. The approach used is classroom action research with 2 cycle stages, the cycle contains several components that take the model design from Kemmis & Mc.Target whose device consists of four components, namely planning (planning), acting (action), observing (observing), and reflecting (reflection). The results of the pre-cycle score obtained by 40%. In the first cycle the score increased to 60%, and in the second cycle there was an increase of 91%. From the score obtained, each stage of the cycle has increased, which means that the use of flipchart learning media is proven to improve the ability to recognize hijaiyah letters for children aged 4-5 years at Primagama Creative Kindergarten Sidoarjo.